Unilateral Anterior Ischemic Optic Neuropathy: Chromatic Pupillometry in Affected, Fellow Non-Affected and Healthy Control Eyes - Herbst, Kristina; Sander, Birgit A.; Lund-Andersen, Henrik; Wegener, Marianne; Hannibal, Jens; Milea, Dan (Frontiers in Neurology, 2013)
The intrinsically photosensitive retinal ganglion cells (ipRGCs) express the photopigment melanopsin, which is sensitive to blue light. Previous chromatic pupillometry studies have shown that the post-illumination response is considered an indicator of the melanopsin activation. The aim of this study was to investigate the ipRGC mediated pupil response in patients with a unilateral non-arteritic anterior ischemic optic neuropathy (NAION). Consensual pupil responses during and after exposure to continuous 20 s blue (470 nm) or red (660 nm) light of high intensity (300 cd/m2) were recorded in each eye for 10 patients. Comparisons were performed both intra-individually (affected versus non-affected eyes) and inter-individually (compared with healthy controls). The pupil response was calculated both during the illumination and during the post-illumination phase. The pupil responses to blue and red colours were significantly reduced in the NAION-affected eyes, compared with the fellow non-affected eyes. When comparing the affected eyes with the healthy control eyes, the post-illumination responses were not significantly different. In addition, the post-illumination pupil responses after blue light exposure were increased in the fellow non-affected patients’ eyes, compared with the healthy controls. However, significance was only reached for the late post-illumination response. In conclusion, chromatic pupillometry disclosed reduced post-illumination pupil responses in the NAION-affected eyes, compared with the non-affected fellow eyes, suggesting dysfunction of the ipRGCs. Compared with the responses of the healthy controls, the blue light post-illumination pupil responses were similar in the affected eyes and increased in the fellow non-affected eyes. This suggests a possible adaptive phenomenon, involving the ipRGCs of both eyes after unilateral NAION.